Development of a SFTSV DNA vaccine that confers complete protection against lethal infection in ferrets - Jeong-Eun Kwak (Nature Portfolio, 2019)
Severe fever with thrombocytopenia syndrome virus (SFTSV) is an emerging tick-borne virus with no specific treatment or vaccine available. Here, the authors develop a DNA vaccine for SFTSV that is protective against lethal challenge in ferrets and show that anti-envelope antibodies are important for protection.